The language use of Bidayuh families in kampung Sira, Padawan : a case study - Helen, Anak Abang. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The purpose of this study was to find out the common language used by the families in Kampung Sira, Padawan. It was also aim to see whether there is a shift in the use of language in the kampung. The participants in this study are three Bidayuh families in which the families having intra-ethnic marriages. This study used interview and observation data collection method. Findings in this study showed that the common language being used by the families are Bidayuh Pinyawa’ and Bahasa Melayu. The shift in language use did happened. It was also found out that there are three main reasons influencing the language use of the participants which were demographic factor, familiarity and ethnicity. Eventhough the younger generation in the families do not speak Bidayuh, it is discovered that their positive attitude towards their native language is still intact.